1996
DOI: 10.1107/s0909049595013288
|View full text |Cite
|
Sign up to set email alerts
|

MAD Phasing Strategies Explored with a Brominated Oligonucleotide Crystal at 1.65Å Resolution

Abstract: The crystal structure of a brominated oligonucleotide d(CGCG(Br)CG), chemical formula C(114)N(48)O(68)P(10)Br(2), has been analysed by multiwavelength anomalous dispersion (MAD) methods. The oligonucleotide crystallizes in space group P2(1)2(1)2(1) with a = 17.97, b = 30.98, c = 44.85 A, alpha = beta = gamma 90 degrees . Data to a resolution of 1.65 A were collected at four wavelengths about the K-absorption edge of the bromine atom (lambda(1) = 0.9323 A, a reference wavelength at the long-wavelength side of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 12 publications
2
30
0
Order By: Relevance
“…It is evident that even a well measured two-wavelength solution can still provide good phasing information as can be seen from solution (j). This supports the observations of Peterson et al (1996), who successfully obtained a fully interpretable electron-density map of a brominated oligonucleotide using only two wavelengths. The poor experimental RSCCs obtained from solution (i) are attributed to poor wavelength calibration of the !…”
Section: Multan E-mapsupporting
confidence: 77%
See 2 more Smart Citations
“…It is evident that even a well measured two-wavelength solution can still provide good phasing information as can be seen from solution (j). This supports the observations of Peterson et al (1996), who successfully obtained a fully interpretable electron-density map of a brominated oligonucleotide using only two wavelengths. The poor experimental RSCCs obtained from solution (i) are attributed to poor wavelength calibration of the !…”
Section: Multan E-mapsupporting
confidence: 77%
“…The morphology of the crystal used in this experiment would have indeed been helpful in reducing these errors. Peterson et al (1996) demonstrated this clearly by measuring data at the f HH peak of the Br K edge with an aligned crystal of a brominated oligonucleotide and with the same crystal misaligned. Using information from only two wavelengths, they found that inclusion of the misaligned-crystal data gave an effectively uninterpretable map, whereas inclusion of the aligned-crystal data provided clearly better maps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAD method relies for its success on the careful measurement of anomalous differences (Peterson et al, 1996) and its success is highly dependent on the characteristics of the source. The third-generation source at Elettra, Trieste, Italy, has a stable, intense beam, and data collected there yielded MAD phases which, in combination with density modi®cation and histogram matching, yielding a very clear electron-density map by the methods described here.…”
Section: Introductionmentioning
confidence: 99%
“…However, MAD experiments have generally used three or more wavelengths to reach a least-squares determination of the phase angle, which puts increased demand on the highly scarce synchrotron radiation beamtime. In a recent effort to minimize this demand, several strategies for a MAD experiment have been explored and it is likely that at least in some cases the requirement could be reduced to data collection at two wavelengths (Peterson et at., 1996). Therefore, there have been great efforts to resolve the phase ambiguity arising from a one-wavelength anomalous scattering (OAS) technique without using additional diffraction data.…”
Section: Introductionmentioning
confidence: 99%